Intermediate mass black hole formation in compact young massive star clusters. Issue 4 (21st November 2020) - Rizzuto, Francesco Paolo; Naab, Thorsten; Spurzem, Rainer; Giersz, Mirek; Ostriker, J P; Stone, N C; Wang, Long; Berczik, Peter; Rampp, M
ABSTRACT: Young dense massive star clusters are promising environments for the formation of intermediate mass black holes (IMBHs) through collisions. We present a set of 80 simulations carried out with nbody6 ++gpu of 10 models of compact 7 × 10^4 M_ star clusters with half-mass radii R h ≲ 1 pc, central densities ρ _core 10^5 M_ pc^-3, and resolved stellar populations with 10 per cent primordial binaries. Very massive stars (VMSs) up to 400 M_ grow rapidly by binary exchange and three-body scattering with stars in hard binaries. Assuming that in VMS–stellar black hole (BH) collisions all stellar material is accreted on to the BH, IMBHs with masses up to M_BH 350 M_ can form on time-scales of ≲15 Myr, as qualitatively predicted from Monte Carlo mocca simulations. One model forms an IMBH of 140 M_ by three BH mergers with masses of 17:28, 25:45, and 68:70 M_ within ∼90 Myr. Despite the stochastic nature of the process, formation efficiencies are higher in more compact clusters. Lower accretion fractions of 0.5 also result in IMBH formation. The process might fail for values as low as 0.1. The IMBHs can merge with stellar mass BHs in intermediate mass ratio inspiral events on a 100 Myr time-scale. With 10 5 stars, 10 per cent binaries, stellar evolution, all relevant dynamical processes, and 300 Myr simulation time, our large suite of 80 simulations indicate another rapid IMBH formation channel in young and compact massive star clusters.